Life-cycle exposure to environmental copper pyrithione causes multigenerational developmental and reproductive toxicity in medaka - Sutapa Debi; Can Tang; Mingfeng Li; Hongdong Fang; Jiezhang Mo; Wenhua Liu (Marine Pollution Bulletin, 2026)

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Waste paper-spent coffee grounds synergistically derived carbonized cellulose aerogel for multifunctional phase change materials: Enhancing thermal energy storage, Joule/solar heating, and electromagnetic shielding - Lihang Yang; Yutao Wang; Mingfeng Chen; Dehao Li; Feng Wang; Liyuan Zhang; Yu Liang; Renjie Chen; Jun Li (Biomass and Bioenergy, 2026)

Physics-informed neural network for predicting reaction kinetics of quinoline hydrodenitrogenation - Shihao Wang; Tao Li; Yuelin Xu; Wenbin Chen; Xiaoqian Dang; Wei Zhang; Chen Zhang; Cuiqing Li; Yong Luo; Feng Liu; Mingfeng Li (Fuel, 2026)

Probabilistic dual-dimensional seismic performance assessment of large-diameter shield tunnels considering lining–internal structure interaction - Peng Liu; Zude Ding; Mingfeng Lei; Shunguo Wang; Runtao Li (Tunnelling and Underground Space Technology, 2026)

Effect of Real-Time High-Temperature on T-H-M Coupled Properties of Rock–Concrete Interfaces under Shear Condition - Chaojun Jia; Haiwei Shang; Pan Li; Yanni Zheng; Chenghua Shi; Mingfeng Lei (Transportation Geotechnics, 2026)

Corrigendum to ‘Study on nutrient release characteristics of infiltration biochar fertilizer coated by cross-linked chitosan’ [J. Environ. Chem. Eng. 13 (6) (2025) 120190] - Pinghui Wei; Xinyuan Fu; Mingfeng Wang; Weiwei Liu; Qingfa Zhang; Bin Li; Zhong Ma (Journal of Environmental Chemical Engineering, 2026)

Valorization of rice husk biochar as a dual-confined slow-release fertilizer: Synergistic effects of pore-throat constriction and active-site engineering - Yuyang Cong; Dongni Qiu; Jie Li; Mingfeng Wang; Donghai Wang; Zhiwen Chen; Ke Zhang (Journal of Environmental Chemical Engineering, 2026)

Progress on the addition of exogenous lipids to surimi: A review - Li Yuan; Mingfeng Xu; Abdul Razak Monto; Wengang Jin; Nannan Zhou; Zhiyu Xiong; Tong Shi; Ruichang Gao (Food Chemistry, 2026)

DirecMamba-MoE: directional Mamba with mixture-of-experts for remote-sensing image semantic segmentation - Mingfeng Li; Lei Cui (International Journal of Remote Sensing, 2026)

Enhancement of macadamia protein solubility and functionality using combined pH-shift-heat treatment: Role of ionic environment (PBS vs water) - Xixiang Shuai; Mingfeng Fang; David Julian McClements; Tingting Chen; Zhipan Wang; Liqing Du; Ming Zhang; Wei Zhou; Taotao Dai; Jihua Li; Jun Chen (Food Chemistry, 2026)

Effects of ultrasound-assisted emulsification and enzyme-catalyzed cross-linking on the structural, rheological and digestive properties of myofibrillar protein-peanut oleosome emulsion gels - Maria Rahman; Ruixi Li; Shahzad Farooq; Mingfeng Xu; Sida Fu; Rongrong Yu (Food Hydrocolloids, 2026)

GNSS/MEMS INS tightly coupled algorithm for agricultural machinery navigation enhanced by random forest-based behavioral state awareness - Yihang Feng; Guanwen Huang; Mingfeng Wang; Xin Li; Zhenhong Li; Hang Li; Kai Zhang; Ce Jing (Computers and Electronics in Agriculture, 2026)

Comparative analysis of fully-coupled towing simulation for a 15MW floating wind turbine using FAST2AQWA method - Mingsheng Chen; Suqian Liu; Xingyu Jiang; Mingfeng Hu; Zhuo Li; Jiale Jiang; Junyu Li (Ocean Engineering, 2026)

Optimizing harvest aid applications for mechanical cotton harvesting: A meta-analysis of defoliation–yield trade-offs driven by crop physiology and environmental factors - Zhenwang Zhang; Yukun Wang; Xinghua Yu; Keke Yu; Huijie Hou; Qinghua Liao; Kexin Li; Zhijie Shi; Jianxin Dong; Guodong Chen; Sumei Wan; Shanwei Lou; et al. (Field Crops Research, 2026)

CYP321A9 mediates the metabolism of two diamide insecticides, chlorantraniliprole and tetrachlorantraniliprole in Spodoptera frugiperda - Wenjing Cao; Mingfeng Huang; Yongheng Zhang; Meng Long; Xuesheng Li (Pesticide Biochemistry and Physiology, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

In situ therapeutic vaccine gel induces pyroptosis and remodels tumor microenvironment to prevent postoperative hepatocellular carcinoma recurrence and metastasis - Liangdi Jiang; Faisal Raza; Shiqi Yang; Kunwei Li; Hang Xiao; Wenjing Chen; Jing Su; Mingfeng Qiu (Chemical Engineering Journal, 2026)

Study on nitrogen and phosphorus adsorption from biogas slurry by biochars derived from different feedstocks - Jingjing Luo; Wenyu Jiang; Huan Ma; Mingfeng Wang; Qingfa Zhang; Bin Li; Weiwei Liu (Environment, Development and Sustainability, 2025)

Study on nutrient release characteristics of infiltration biochar fertilizer coated by cross-linked chitosan - Pinghui Wei; Xinyuan Fu; Mingfeng Wang; Weiwei Liu; Qingfa Zhang; Bin Li; Zhong Ma (Journal of Environmental Chemical Engineering, 2025)

Insight into metal-support interactions of NiMo hydrodesulfurization catalysts and their variations during application - Wenhui He; Yanjuan Xiang; Mudi Xin; Weiming Zhai; Sicong Qiao; Nan Zhang; Limei Qiu; Siyang Yan; Feng Liu; Jianqiang Wang; Guangtong Xu; Jiaxu Liu; et al. (Chemical Engineering Journal, 2025)

Improving stability and UV protection properties of phycocyanin nanoparticle-based Pickering emulgels via amorphous cationic starch complexation - Yacheng Hao; Jiahao Mei; Dongfang Ling; Zhe Zhang; Sai Li; Zhiyong Gong; Xin Liu; Mingfeng Xu; Yilin Lin; Rongrong Yu (Carbohydrate Polymers, 2025)

CDC6 promotes the development and progression of clear cell renal cell carcinoma via upregulating RRM2 - Tianpeng Xie; Zanxuan Deng; Youping Ding; Peng Peng; Pan Rao; Yanqun Huang; Lizhen Li; Gaode Zou; Xiaofeng Zou; Mingfeng Xiang (Human Cell, 2025)

Morphology-Controlled Alumina-Supported MoS2 catalysts for enhancing hydrogenation and hydrodenitrogenation via metal clusters - Chenxi Li; Aiguo Zheng; Hong Nie; Wei Han; Mingfeng Li; Anpeng Hu; Le Zhang; Huifeng Li (Fuel, 2025)

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

Examining how green space patterns affect noise distribution in urban areas with varying built-up densities - Mingfeng Zhang; Yuanxiang Wu; Mengmeng Li; Qi Meng; Jian Kang (Journal of Environmental Management, 2025)

Tenebrio molitor powder enhances gelation properties of Penaeus vannamei myofibrillar protein: Mechanistic insights into structural optimization and digestibility - Mingfeng Xu; Ruixi Li; Mengting Li; Chaoyi Duan; Yinyin Wei; Xiangxiang Ni; Xiu Wang; Sida Fu; Rongrong Yu (Food Chemistry, 2025)

Influence of aromatics on the hydrodesulfurization reaction pathway of the NiMo/Al2O3 catalyst using quasi-in situ characterization techniques - Longxin Gao; Wenhui He; Weiming Zhai; Mudi Xin; Wei Wang; Yanjuan Xiang; Hui Yuan; Sa Wang; Feng Liu; Guangtong Xu; Limei Qiu; Mingfeng Li (Fuel, 2025)

IRBITs, signaling molecules of great functional diversity - Ying Liu; Xuhui Feng; Han Wu; Tianxiang Gui; Mingfeng Fu; Xudong Luo; Lei Zhao; Li-Ming Chen (Pflügers Archiv - European Journal of Physiology, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Isolation and structural elucidation of two novel lignans from the flowers of Gardenia jasminoides with potent α-glucosidase inhibitory activity - Qingsen Shao; Huiyu Li; Mingfeng Li; Wei Yi; Qiugui Zhou; Lijuan Zheng; Meng Wang; Hong-mei Hu; Chao Wen; Yun Tang; Wei Li (Phytochemistry Letters, 2025)

Identification of volatile indicators for quality deterioration of Yu-Shiang Shredded pork after reheating based on HS-GC-IMS and intelligent sensory evaluation - Chunyuan Ping; Honglian Hu; Jicai Bi; Xiang Li; Yuwen Yi; Mingfeng Qiao (International Journal of Gastronomy and Food Science, 2025)

Structure-performance relationship between zeolites properties and hydrocracking performance of tetralin over NiMo/Al2O3-Y catalysts: A machine-learning-assisted study - Wei Wang; Mingfeng Li; Yang Zhang; Kang Qin; Li Zhuang; Ping Yang; Hong Nie (Fuel, 2025)

Changes of soil nitrate accumulation and the abundance and structure of nitrogen cycling microbial communities during long-term solar greenhouse vegetable cultivation - Mingxia Yang; Ningning Zhou; Mingfeng Li; Zhujun Chen; Jianbin Zhou; Xiaofang Deng (Journal of Soils and Sediments, 2025)

Redox state of NAD modulates the activation of Na-bicarbonate cotransporter NBCe1-B via IRBIT and L-IRBIT - Tianxiang Gui; Ying Liu; Mingfeng Fu; Han Wu; Pan Su; Xuhui Feng; Mengmeng Zheng; Zixuan Huang; Xudong Luo; Walter F. Boron; Li-Ming Chen (Science China Life Sciences, 2025)

Promotion mechanism of rare-earth elements doping on performance of CaO/CeO2 sorbent for high temperature CO2 capture - Yunfeng Li; Jiarui Wu; Feng Liu; Weiwei Liu; Bin Li; Qingfa Zhang; Mingfeng Wang; Haiping Yang; Zhen Fang; Zhong Ma (Chemical Engineering Journal, 2025)

Comparative study of failure mechanism of CFRP partially confined normal strength concrete (NSC) and UHPC cylinders under axial compression - Wanye Li; Yao Lu; Meizhong Wu; Peng Wang; Weiwen Li; Xingquan Wang; Mingfeng Kai; Jing Yu (Engineering Structures, 2025)

Genetic characterization of a novel HIV-1 circulating recombinant form (CRF162_cpx) involving CRF01_AE, CRF07_BC and subtype B in Guangdong, China - Yun Lan; Linghua Li; Mingfeng Xiao; Yaqing Lin; Xuemei Ling; Feng Li; Fengyu Hu (Virus Genes, 2025)

Motion adaptive vision-based vibration measurement and modal identification for the roof masts of a tall building - Mingfeng Huang; Xianzhe Li; Kang Cai; Ahsan Kareem (Engineering Structures, 2025)

Characteristics and spatial-temporal dynamics in agronomic landscape: Case study of Guangrong watershed, Northeast China - Renjian Qiu; Mingfeng Kong; Zhenfeng Lei; Jinhao Shi; Zhaoyi Li; Haifeng Zheng (Applied Geography, 2025)

A leader-adaptive particle swarm optimization with dimensionality reduction strategy for feature selection - Shanshan Yang; Bo Wei; Li Deng; Xiao Jin; Mingfeng Jiang; Yanrong Huang; Feng Wang (Swarm and Evolutionary Computation, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Prognostic impact of DTA mutation and co-occurring mutations in patients with myelodysplastic syndrome - Min Wang; Ping Chen; Daqi Li; Mingfeng Zhao (Molecular Biology Reports, 2024)

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

Polyoxometalate-mediated film bearing near-infrared photothermal self-healing property for seawater desalination - Shuangyu Wu; Dongdong Li; Mingfeng Wei; Bao Li; Lixin Wu (Chemical Engineering Journal, 2024)

Experimental Investigation on Freeze–Thaw Damage Mechanism of Xiyu Conglomerate Under Uniaxial Cyclic Loading - Chaojun Jia; Ruifeng Pang; Qiang Zhang; Mingfeng Lei; Chenghua Shi; Wenxin Li (Rock Mechanics and Rock Engineering, 2024)

Optimizing radiation capture in machine-harvested cotton: A functional-structural plant modelling approach to chemical vs. manual topping strategies - Shenghao Gu; Shuai Sun; Xuejiao Wang; Sen Wang; Mingfeng Yang; Jie Li; Paerhati Maimaiti; Wopke van der Werf; Jochem B. Evers; Lizhen Zhang (Field Crops Research, 2024)

In situ tracking of the impact of atomic-scale fragment structures on MoS2 nanocrystals for high-stability industrial NiMo/γ-Al2O3 hydrodesulfurization catalysts - Wenhui He; Mudi Xin; Yanjuan Xiang; Weiming Zhai; Zheng Chen; Limei Qiu; Aiguo Zheng; Feng Liu; Le Zhang; Guangtong Xu; Mingfeng Li (Chemical Engineering Journal, 2024)

Novel benzothiazole-based fluorescent probe for efficient detection of Cu2+/S2− and Zn2+ and its applicability in cell imaging - Linxiu Zhao; Junli Shi; Yongzheng Liu; Mingfeng Han; Shengling Li; Duanlin Cao (Analytica Chimica Acta, 2024)

Formula model established through field application of glass slides and rapid analysis of pesticide residues in vegetables by ion mobility spectrometry - Yong Mei; Mingfeng Huang; Wayne Jiang; Gaoqing Yuan; Xuesheng Li (Food Control, 2024)

Cotton crop transpiration reveals opportunities to reduce yield loss when applying defoliants for efficient mechanical harvesting - Yongfan Chen; Jochem B. Evers; Mingfeng Yang; Xuejiao Wang; Zeshan Zhang; Shuai Sun; Yutong Zhang; Sen Wang; Fen Ji; Dao Xiang; Jie Li; Chunrong Ji; et al. (Field Crops Research, 2024)

A new strategy for enhanced phosphate removal from waters using ferric oxide impregnated biochar - Lili Dong; Yan Li; Xinli Wen; Mingfeng Zhao; Le Zhang; Mengmeng Zhu; Shunli Wan (Chemical Engineering Journal, 2024)

Influence of large-scale climate indices and regional meteorological elements on drought characteristics in the Luanhe River Basin - Min Li; Zilong Feng; Mingfeng Zhang; Yuhang Yao (Atmospheric Research, 2024)

Is seasonal closure an effective way to conserve oceanic squids—Taking Chinese autonomic seasonal closure on the high seas as an example - Mingfeng Jiang; Jintao Wang; Gang Li; Bilin Liu; Xinjun Chen (Fisheries Research, 2024)

Design of active phase structure with high activity and stability in residue hydrotreating reactions - Yanzi Jia; Anpeng Hu; Dawei Hu; Mingfeng Li; Huifeng Li; Qinghe Yang; Zhiwei Liu; Zhicai Shao; Shuangqin Zeng; Xinqiang Zhao; Yifan Wang (Fuel, 2024)

Effective reduction of hydrogen consumption in ultra-deep hydrodesulfurization of diesel: Deep insights into the effect of thermodynamic limitations during hydrotreating - Yubai Zhang; Feng Liu; Wenbin Chen; Wei Han; Weiming Zhai; Yutao Lu; Mingfeng Li (Fuel, 2024)

S-dinotefuran affects the social behavior of honeybees (Apis mellifera)and increases their risk in the colony - Fu Zhang; Wenjing Cao; Yongheng Zhang; Jie Luo; Jiangan Hou; Lichao Chen; Guoqiang Yi; Honghong Li; Mingfeng Huang; Linxi Dong; Xuesheng Li (Pesticide Biochemistry and Physiology, 2023)

Performance Comparison of Sea Cucumber Detection by the Yolov5 and DETR Approach - Xin Yuan; Shutong Fang; Ning Li; Qiansheng Ma; Ziheng Wang; Mingfeng Gao; Pingpeng Tang; Changli Yu; Yihan Wang; José-Fernán Martínez Ortega (Journal of Marine Science and Engineering, 2023)
Sea cucumber detection represents an important step in underwater environmental perception, which is an indispensable part of the intelligent subsea fishing system. However, water turbidity decreases the clarity of underwater images, presenting a challenge to vision-based underwater target detection. Therefore, accurate, real-time, and lightweight detection models are required. First of all, the development of subsea target detection is summarized in this present work. Object detection methods based on deep learning including YOLOv5 and DETR, which are, respectively, examples of one-stage and anchor-free object detection approaches, have been increasingly applied in underwater detection scenarios. Based on the state-of-the-art underwater sea cucumber detection methods and aiming to provide a reference for practical subsea identification, adjacent and overlapping sea cucumber detection based on YOLOv5 and DETR are investigated and compared in detail. For each approach, the detection experiment is carried out on the derived dataset, which consists of a wide variety of sea cucumber sample images. Experiments demonstrate that YOLOv5 surpasses DETR in low computing consumption and high precision, particularly in the detection of small and dense features. Nevertheless, DETR exhibits rapid development and holds promising prospects in underwater object detection applications, owing to its relatively simple architecture and ingenious attention mechanism.

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Numerical Simulation Study on Ship–Ship Interference in Formation Navigation in Full-Scale Brash Ice Channels - Chang Xie; Li Zhou; Mingfeng Lu; Shifeng Ding; Xu Zhou (Journal of Marine Science and Engineering, 2023)
Formation navigation in brash ice channels is increasingly utilized by merchant vessels in the Arctic and Baltic Sea, offering benefits such as improved efficiency and reduced carbon emissions. However, ship–ship interference poses a significant challenge to this method, impacting resistance performance. This paper presents full-scale simulations using the CFD–DEM coupling method in brash ice channels, which is validated by comparing simulation results with ice tank measurements. By varying the distance between two ships from 0.05 to 5 ship lengths, ship–ship interference in full-scale brash ice channels is analyzed using the CFD–DEM coupling strategy. The study examines hydrodynamic and ship–ice interactions, ice resistance effects, and simulation results. It is found that ship-to-ship distance significantly influences the velocity field, dynamic pressure distribution on the hull, and hydrodynamic interaction forces. Distances less than one ship length result in increased water resistance for the forward ship and decreased resistance for the rear ship. The forward ship demonstrates favorable interference with the ice accumulation of the rear ship. When distances are less than two ship lengths, the ice resistance of the forward ship remains mostly unaffected, while the ice resistance of the rear ship decreases as the distance decreases. These insights enhance our understanding of ship–ship interference in formation navigation, aiding in the optimization of brash ice channel navigation strategies.

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

Experimental and DEM simulations of the mechanical properties of rock under freeze–thaw cycles - Jun Yu; Qiang Zhang; Chaojun Jia; Mingfeng Lei; Chenyang Zhao; Ruifeng Pang; Zong Li; Tao Zeng (Cold Regions Science and Technology, 2023)

Machine Learning-Based Prediction of Dynamic Responses of a Tower Crane under Strong Coastal Winds - Qiang Li; Weijie Fan; Mingfeng Huang; Heng Jin; Jun Zhang; Jiaxing Ma (Journal of Marine Science and Engineering, 2023)
With the rapid development of the construction industry, tower cranes are increasingly used in coastal engineering. However, due to the complexity of their operating environment, tower cranes are vulnerable to typhoons, thunderstorms, and other extreme natural disasters. Therefore, it is becoming increasingly important to carry out safety warnings for the tower crane structure under the action of strong winds. In this paper, a real-time monitoring system for tower responses based on the Internet of things (IoT), which realizes long-term monitoring of the whole process of tower crane operation, was built. Based on the long-term monitoring data and the machine learning algorithm, two tower response prediction models were established. During the transit of super typhoon In-fa, the maximum displacement of the tower structure was predicted in advance, based on the measured wind speed data at the site, which is in good agreement with the displacement data monitored by the IoT. The results show that under strong winds, the non-working tower has a response lag, resulting in the fact that its maximum displacement does not correspond to the maximum wind speed moment at the site. This is mainly due to the weathercock effect of the tower in the non-working condition. The prediction model proposed in this paper can provide timely and effective safety warnings for the tower structure. It also can provide useful engineering references and scientific structural safety warning suggestions for the same type of tower cranes that do not have IoT monitoring systems installed.

Effects of frequencies on the cyclic behavior of marine soft clay under different consolidated stress paths - Mingfeng Li; Ming Dai; Shengnan Yao; Shihu Gao; Guohui Yuan (Marine Georesources & Geotechnology, 2023)

Uplift history of the Northern Tianshan constrained from the inversion of river profiles - Runing Hou; Mei Liu; Ningsheng Chen; MingFeng Deng; Shufeng Tian; Yujia Li; Huayong Ni; Zheng Han (International Journal of Earth Sciences, 2023)

The pore pressure generation and deformation of overconsolidated soft marine clay considering initial static shear effect - Ming Dai; Lin Guo; Mingfeng Li; Tian Jin (Marine Georesources & Geotechnology, 2022)

Strength and structural variations in dredger fill subjected to vacuum dynamic consolidation - You Zhou; Hongtao Fu; Tian Jin; Mingfeng Li; Junfeng Ni (Marine Georesources & Geotechnology, 2022)

Post-cyclic undrained shear behavior of soft marine clay under anisotropic consolidation stress paths - Ming Dai; Xiaobing Li; Ziyang Gao; Mingfeng Li (Marine Georesources & Geotechnology, 2022)

Combining double probability distribution functions to unmix bimodal grain-size distributions of sediments - Rui Xu; Rui Yuan; Donghui Li; Liang Xu; Mingfeng Gu (Arabian Journal of Geosciences, 2022)

Cement replacement with brick powder and concrete powder in sludge solidification - Junfeng Ni; Xiuqing Hu; Feiyu Liu; Chengan Zhu; Li Mingfeng; Jinqiang Jin; Changfei Gou (Marine Georesources & Geotechnology, 2022)

Behaviour of electroosmotic consolidation by electrode configuration and fracture grouting - Yunguo Du; Chao Zhang; Changfei Gou; Wenwen Wu; Xiaobing Li; Xiuqing Hu; Wang Chaoliang; Li Mingfeng (Marine Georesources & Geotechnology, 2022)

Effect of initial deviatoric stress on anisotropy of marine clay during principal stress rotation - Heng Zhuang; Xiuqing Hu; Lin Guo; Li Mingfeng; Wang Chaoliang; Hongke Du; Jingqiang Jin (Marine Georesources & Geotechnology, 2022)

Oceanic vertical mixing of the lower halocline water in the Chukchi Borderland and Mendeleyev Ridge - Long Lin; Hailun He; Yong Cao; Tao Li; Yilin Liu; Mingfeng Wang (Acta Oceanologica Sinica, 2021)

The optimal combination form of vacuum pre-loading combined with electro-osmosis and with dynamic compaction method on the improvement of dredged slurry - Xiuqing Hu; Ziyang Gao; Feiyu Liu; Yu Tao; Donghai Xu; Yunguo Du; Changfei Gou; Mingfeng Li (Marine Georesources & Geotechnology, 2021)

The effects of initial deviatoric stress on anisotropy of marine clay and strain components - Heng Zhuang; Mingfeng Li; Chaoliang Wang; Lin Guo; Dikang Zhang; Hongke Du; Yunguo Du (Marine Georesources & Geotechnology, 2021)

Behaviour of thick marine deposits subjected to vacuum combined with surcharge preloading - Dikang Zhang; Hongtao Fu; Jun Wang; Dongqi Zhu; Xiuqing Hu; Yunguo Du; Changfei Gou; Chaoliang Wang; Mingfeng Li; Hai Wu (Marine Georesources & Geotechnology, 2021)

Antisense oligonucleotide technology can be used to investigate a circular but not linear RNA-mediated function for its encoded gene locus - Zhenxing Song; Ruirui Jia; Mingfeng Tang; Fei Xia; Haiyang Xu; Zhengguo Li; Chuan Huang (Science China Life Sciences, 2021)

Assessing SARS-CoV-2 RNA levels and lymphocyte/T cell counts in COVID-19 patients revealed initial immune status as a major determinant of disease severity - Mingfeng Han; Mengyuan Xu; Yafei Zhang; Zhongping Liu; Shasha Li; Tengfei He; Jinsong Li; Yong Gao; Wanjun Liu; Tuantuan Li; Zixiang Chen; Xin Huang; et al. (Medical Microbiology and Immunology, 2020)

Improved robust tensor principal component analysis for accelerating dynamic MR imaging reconstruction - Mingfeng Jiang; Qiannan Shen; Yang Li; Xiaocheng Yang; Jucheng Zhang; Yaming Wang; Ling Xia (Medical & Biological Engineering & Computing, 2020)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Advanced glycation end products promote proliferation and suppress autophagy via reduction of Cathepsin D in rat vascular smooth muscle cells - Mingfeng Ma; Xiaofan Guo; Ye Chang; Chao Li; Xin Meng; Si Li; Zhen-Xian Du; Hua-Qin Wang; Yingxian Sun (Molecular and Cellular Biochemistry, 2015)

Sec Pathway Influences the Growth of Deinococcus radiodurans - Liangyan Wang; Hongmei Tan; Kaiying Cheng; Mingfeng Li; Xin Xu; Jing Wang; Yuejin Hua (Current Microbiology, 2015)

Pyruvate decarboxylase and alcohol dehydrogenase overexpression in Escherichia coli resulted in high ethanol production and rewired metabolic enzyme networks - Mingfeng Yang; Xuefeng Li; Chunya Bu; Hui Wang; Guanglu Shi; Xiushan Yang; Yong Hu; Xiaoqin Wang (World Journal of Microbiology and Biotechnology, 2014)

Obesity-related genetic variants, human pigmentation, and risk of melanoma - Xin Li; Liming Liang; Mingfeng Zhang; Fengju Song; Hongmei Nan; Li-E Wang; Qingyi Wei; Jeffrey E. Lee; Christopher I. Amos; Abrar A. Qureshi; Jiali Han (Human Genetics, 2013)

Impacts of global emissions of CO, NO x , and CH4 on China tropospheric hydroxyl free radicals - Mingfeng Su; Yunping Lin; Xinqiang Fan; Li Peng; Chunsheng Zhao (Advances in Atmospheric Sciences, 2012)

PDGF-induced airway smooth muscle proliferation is associated with Human antigen R activation and could be weakened by AMPK activation - Pengju Zhang; Mingfeng Cao; Yi Liu; Zhimei Lv; Qingrui Yang; Xiaoyan Lin; Huaichen Li; Qiang Wan (Molecular Biology Reports, 2012)

Three nth homologs are all required for efficient repair of spontaneous DNA damage in Deinococcus radiodurans - Xiaoting Hua; Xin Xu; Mingfeng Li; Chao Wang; Bing Tian; Yuejin Hua (Extremophiles, 2012)

Major Energy Plants and Their Potential for Bioenergy Development in China - Xiaofeng Li; Shenglin Hou; Man Su; Mingfeng Yang; Shihua Shen; Gaoming Jiang; Dongmei Qi; Shuangyan Chen; Gongshe Liu (Environmental Management, 2010)

A high-density intervarietal map of the wheat genome enriched with markers derived from expressed sequence tags - Shulin Xue; Zhengzhi Zhang; Feng Lin; Zhongxin Kong; Yong Cao; Chunjun Li; Hongying Yi; Mingfeng Mei; Huilan Zhu; Jizhong Wu; Haibin Xu; Dongmei Zhao; et al. (Theoretical and Applied Genetics, 2008)